POSTCOVID DEPRESSION: DIAGNOSIS AND WAYS TO OVERCOME IT - Pitulei, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
The article deals with the problem of postcovid depression. The main diagnostic criteria and symptoms of depressive disorder are outlined. It is indicated that the basic symptoms include: depressed mood, loss of curiosity and pleasure from daily activities, increased fatigue, loss of energy and decreased activity. The risk factors that most influence the formation of depressive disorders are analyzed. These factors include: job loss, divorce, loss of relatives, high levels of personal anxiety, and stressful life events. The main goal of therapy in patients with VDR is complete functional recovery and return to the premorbid state. The difficulty of treating depressive disorders lies in the lack of complete recovery in the case of severe or complicated forms of depressive disorders. The author identifies the main emotional and cognitive signs of depressive disorder, namely: low or increased mood, feelings of anxiety and unreasonable anxiety, irritability or manifestations of anger towards yourself or other people, repeated negative thoughts about yourself, about drug addicts and the future, reduced concentration of attention, apathy, inattention. Recovery from depression is not the absence of negative affective symptoms, but the restoration of normal emotional functioning, the ability to be yourself and experience positive emotions. The goal of psychotherapy for depression is to change the patient's negative thoughts, emotional state and mood.